Frankenstein, or, The modern Prometheus - Shelley, Mary Wollstonecraft 1797-1851 (A Tor Book, 1988)
A monster assembled by a scientist from parts of dead bodies develops a mind of his own as he learns to loathe himself and hate his creator.